2019
DOI: 10.1037/xan0000211
|View full text |Cite
|
Sign up to set email alerts
|

Rats engage in suboptimal choice when the delay to food is sufficiently long.

Abstract: Numerous examples in the decision-making literature demonstrate that animals sometimes make choices that are not in their long-term best interest. One particular example finds pigeons preferring a lowprobability alternative in lieu of a high-probability alternative, referred to as suboptimal choice. Although there is ample evidence that pigeons engage in such suboptimal choice, there is currently weak evidence (at best) that rats also do so. Cunningham and Shahan's (2018) temporal information-theoretic model s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
66
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(80 citation statements)
references
References 43 publications
11
66
3
Order By: Relevance
“…Part of the difficulty stems from the complexity of the task, from its large number of features including various stimuli, delays, and probabilities. Previous research has examined the role of, among other variables, the terminal link delays (which seem not to affect preference except when very short, for example, 1.5 s; see Cunningham & Shahan, ; Fortes et al, ; Kendall, ; Spetch et al, ; Zentall & Stagner, ); the degree of contiguity between choice and the terminal link stimulus onset (with gaps decreasing or reversing the preference for the suboptimal alternative; see McDevitt et al, ; Vasconcelos et al, ); and the response requirement during the initial links (VIs or FRs with parameter greater than 1 reduce or even prevent suboptimal behavior; see Fantino et al, ; Kendall, ; Zentall et al, ). However, most models of suboptimal choice rely on the predictability of the signals in the terminal link of the suboptimal alternative and the difference in the overall rate of reinforcement between alternatives (Cunningham & Shahan, ; Fortes et al, ; Stagner & Zentall, ).…”
Section: Discussionmentioning
confidence: 99%
“…Part of the difficulty stems from the complexity of the task, from its large number of features including various stimuli, delays, and probabilities. Previous research has examined the role of, among other variables, the terminal link delays (which seem not to affect preference except when very short, for example, 1.5 s; see Cunningham & Shahan, ; Fortes et al, ; Kendall, ; Spetch et al, ; Zentall & Stagner, ); the degree of contiguity between choice and the terminal link stimulus onset (with gaps decreasing or reversing the preference for the suboptimal alternative; see McDevitt et al, ; Vasconcelos et al, ); and the response requirement during the initial links (VIs or FRs with parameter greater than 1 reduce or even prevent suboptimal behavior; see Fantino et al, ; Kendall, ; Zentall et al, ). However, most models of suboptimal choice rely on the predictability of the signals in the terminal link of the suboptimal alternative and the difference in the overall rate of reinforcement between alternatives (Cunningham & Shahan, ; Fortes et al, ; Stagner & Zentall, ).…”
Section: Discussionmentioning
confidence: 99%
“…Since Kendall's (1974) initial demonstration, suboptimal choice has been extensively studied in pigeons (see McDevitt et al, 2016 andZentall, 2016b), and has been observed in monkeys (e.g., Blanchard, Hayden, & Bromberg-Martin, 2015;Bromberg-Martin & Hikosaka, 2009;Smith, Beran, & Young, 2017) and starlings (e.g., Vasconcelos, Monteiro, & Kacelnik, 2015). The procedure has also been used with rats, but the results have been less consistent (e.g., Mazur, 2007;Trujano & Orduna, 2015; but see Cunningham & Shahan, 2019). Human participants, however, have received little empirical attention despite the suggestion that the suboptimal choice task "provides a reasonable analog to human commercial gambling behavior" (Zentall, 2016a, p. 110, cf.…”
Section: Introductionmentioning
confidence: 99%
“…Past research has demonstrated preference for an alternative which produces stimuli that signal the future presence or absence of reinforcement over an alternative which does not produce reinforcement-predictive stimuli. This preference has been found in multiple species, including capuchins, rhesus macaques, pigeons, and rats ( Roper and Zentall, 1999 ; Smith et al, 2017 ; Cunningham and Shahan, 2019 ; Smith and Beran, 2020 ). For example, when Roper and Zentall (1999) presented a choice between two alternatives which produced reinforcement equally 50% of the time, pigeons’ choices were more frequently allocated to the alternative which provided reinforcement-predictive stimuli (see Figure 1A ).…”
Section: Introductionmentioning
confidence: 96%
“…This choice preference has been found multiple times in pigeons ( Stagner and Zentall, 2010 ; Zentall and Stagner, 2011 ; Laude et al, 2014 ) and has been likened to gambling behavior demonstrated by humans ( Zentall, 2014 , 2016 ). The present experiments used a similarly structured task to examine adult human preferences for reinforcement predictors and compared findings to choice behavior demonstrated by children ( Lalli et al, 2000 ), monkeys ( Smith et al, 2017 ; Smith and Beran, 2020 ), dogs ( Jackson et al, 2020 ), rats ( Chow et al, 2017 ; Cunningham and Shahan, 2019 ; Jackson et al, 2020 ), and pigeons ( Roper and Zentall, 1999 ; Stagner and Zentall, 2010 ). In Experiment 1, adult human participants showed no preference for reinforcement predictors.…”
mentioning
confidence: 99%